PENINGKATKAN PERILAKU SOSIAL KEAGAMAAN PESERTA DIDIK KELAS 6 SDN SIMOMULYO I SURABAYA MELALUI PENDIDIKAN AGAMA ISLAM - M. S. Badar (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2021)
This PTK study is motivated by the existence of religious activities at SDN Simomulyo I Surabaya such as tartil suroh-suroh juz 'amma, chanting Asmaul Husna, congregational prayer and infaq. These problems were discussed through field study research conducted in grade 6 SDN Simomulyo I Surabaya, with 36 students as respondents. Meanwhile, the data collection method used questionnaires, observation and documentation. The data were obtained by distributing questionnaires with a total of 30 questions and given to 36 students in grade 6. All data were analyzed using a quantitative approach and descriptive statistical analysis. The study shows that: (1) The application of Islamic religious education for 6th grade students of SDN Simomulyo I Surabaya has an average value of = 41.31. This shows that the intensity of students in participating in religious activities is in the High category, which is in the value interval 31–45. (2) The socio-religious behavior of grade 6 students at SDN Simomulyo I Surabaya has an average value of = 37.83. This shows that the socio-religious behavior of students is included in the High category, which is in the value interval 31 - 45. (3) There is an influence of variable X (Implementation of Islamic Education) on variable Y (Religious Social Behavior of Class 6 SDN Simomulyo Students. I Surabaya). Thus it can be said that there is a positive and significant influence between the application of Islamic religious education on the socio-religious behavior of students in grade 6 SDN Simomulyo I Surabaya is accepted.